2001
DOI: 10.1152/ajpendo.2001.280.2.e357
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoceptor-mediated thermogenesis and lipolysis in patients with chronic obstructive pulmonary disease

Abstract: The present study investigated whether development or maintenance of a relatively increased fat mass in normal-weight patients with chronic obstructive pulmonary disease (COPD), despite periods of weight loss, may be related to impaired beta-adrenoceptor-mediated responses in lipid utilization and thermogenesis. Nine COPD patients and nine healthy controls (body mass index: 23.0 +/- 1.3 vs. 23.8 +/- 0.6 kg/m2, not significant; fat mass: 19.0 +/- 2.1 vs. 11.9 +/- 1.5 kg, P < 0.01) received consecutive 30-min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
1
15
1
Order By: Relevance
“…Although no abnormal plasma glucose levels were found in COPD in the current study, the current authors have previously reported the presence of hyperinsulinaemia in moderate-to-severe COPD patients [34]. Impaired glucose tolerance and impaired b-adrenoceptor-mediated lipolysis have been shown for COPD [35,36]. Furthermore, reduced activities of enzymes involved in oxidative substrate metabolism have been found in the vastus lateralis of COPD patients [8].…”
Section: Discussioncontrasting
confidence: 48%
“…Although no abnormal plasma glucose levels were found in COPD in the current study, the current authors have previously reported the presence of hyperinsulinaemia in moderate-to-severe COPD patients [34]. Impaired glucose tolerance and impaired b-adrenoceptor-mediated lipolysis have been shown for COPD [35,36]. Furthermore, reduced activities of enzymes involved in oxidative substrate metabolism have been found in the vastus lateralis of COPD patients [8].…”
Section: Discussioncontrasting
confidence: 48%
“…1 There are indications that the blunted b-adrenergically mediated lipolysis in obesity may be related to an impaired function or a reduced number of adipocyte beta-2 (b 2 ) adrenoceptors. 5,6 b 2 -Adrenoceptors are stimulatory G-protein-coupled (G s ) receptors. The b 2 -adrenoceptor (ADRB2) gene is encoded by an intronless gene on chromosome 5q31-q32.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reduced skeletal muscle activity of 3-hydroxyacyl CoA dehydrogenase, which regulates the b-oxidation of fatty acids, has consistently been shown in normalweight COPD patients [8]. Finally, an impaired badrenoceptor-mediated increase in plasma levels of nonesterified fatty acids was reported in sarcopaenic COPD patients [9], which is suggestive of reduced lipolysis. However, whole-body AFFILIATIONS *Dept of Respiratory Medicine, NUTRIM School for Nutrition, Toxicology and Metabolism, Maastricht University Hospital, Maastricht, and lipolytic rate and differences in lipid kinetics between sarcopaenic and underweight COPD patients have not been studied until now.…”
mentioning
confidence: 91%